2022
DOI: 10.1038/s41598-022-11712-9
|View full text |Cite
|
Sign up to set email alerts
|

Cutting seton versus decompression and drainage seton in the treatment of high complex anal fistula: a randomized controlled trial

Abstract: This study aimed to compare the efficacy between decompression and drainage seton (DADS) and cutting seton (CS) in the treatment of high complex anal fistula. Patients were randomly assigned 1:1 to DADS or CS group. The primary outcome was the rate of wound healing. Second outcomes included time taken to return to work, postoperative pain, the severity of fecal incontinence and other complications. A total of 120 patients with a mean age of 39 years were included. There was no significant difference in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…• Fecal incontinence not to be a complication in long-term outcome with a median follow-up time of 47 months, as it was not seen in otherwise healthy infants and children in our population. Studies on adult FIA treatment confirm higher rates of fecal after cutting seton placement (13,14), which might probably also be the case after decades in discussed populations of infants with FIA and might not have been recorded in previous studies (11). • Hints to postsurgical perianal dermatitis and childhood constipation.…”
Section: Discussionmentioning
confidence: 87%
“…• Fecal incontinence not to be a complication in long-term outcome with a median follow-up time of 47 months, as it was not seen in otherwise healthy infants and children in our population. Studies on adult FIA treatment confirm higher rates of fecal after cutting seton placement (13,14), which might probably also be the case after decades in discussed populations of infants with FIA and might not have been recorded in previous studies (11). • Hints to postsurgical perianal dermatitis and childhood constipation.…”
Section: Discussionmentioning
confidence: 87%
“…This situation can be explained by the tension caused by the seton and the foreign body reaction. When we look at the literature, it is seen that the pain levels of the conventional drainage seton are higher than even the cutting seton [3,11]. However, no study comparing it with stulotomy has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Fistulotomy is still the most successful method for treating simple stulas. However, in complex stulas, cutting seton application, drainage seton placement followed by advanced surgical methods such as video-assisted anal stula treatment (VAAFT), and ligation of the intersphincteric stula tract (LIFT) may be preferred [3,4]. In all surgical methods used, postoperative pain and loss of function are inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to severe pain, high incontinence rates, and patient dissatisfaction, surgeons have been looking for sphincter-sparing, more minimally invasive techniques. Recently, techniques such as laser applications to the anal fistula tract, ligation of intersphincteric fistula tract (LIFT), use of an anal fistula occlusive material, and video-assisted electrocautery of anal fistula (video-assisted anal fistula treatment, or VAAFT) have been used to preserve sphincter function in the treatment of anal fistula [ 9 ].…”
Section: Introductionmentioning
confidence: 99%